Bacteriophage therapy in women with chronic recurrent cystitis caused by multidrug-resistant bacteria: A prospective, observational, comparative study - Denis Krakhotkin; Nikolai Iglovikov; Gideon Blecher; Vladimir Chernylovskyi; Francesco Greco; Svetlana A. Gayvoronskaya; Amr El Meliegy (Current Urology)
Abstract. Objectives. The aim of this study was to evaluate the effects of the combination of bacteriophage therapy with antibiotics and bacteriophage treatment alone on relieving clinical symptoms of chronic recurrent cystitis caused by multidrug-resistant bacteria. Materials and methods. This clinical trial compared the treatment methods of 217 female patients with chronic recurrent cystitis caused by multidrug-resistant bacteria, who were investigated from June 2020 to May 2023. Patients were allocated into 4 groups: group I: received bacteriophage (Sextaphage) therapy alone; group II: received a combination of bacteriophages (Sextaphage) and furazidin; group III: received a combination of bacteriophage (Sextaphage) and furazidin with cefixime; and group IV: received furazidin and cefixime (without bacteriophage). The primary outcome included changes in the acute cystitis symptom scale and the pain visual analog scale, which were completed on days 7 and 14 following treatment. Secondary outcome measures included bladder diary records of urinary symptoms, median voided volumes, level of bacteriuria, and degree of leukocyturia. Results. Initially, 217 female patients were presented during baseline visits. Those who did not meet the criteria inclusions were excluded, and 178 female patients were included in the final analysis. Statistically significant improvements from baseline in acute cystitis symptom scale scores for differential, typical symptoms, and quality of life domains were observed after 14 days of treatment in groups II, III, and IV. The pain level measured on the 14th day with the visual analog scale significantly decreased in groups II, III, and IV compared with group I. The patients of group I had a reduction of mean level bacteriuria of Escherichia coli from 106 to 102 CFU/mL at 14 days of therapy. Significant improvement of voided volume from baseline was observed in groups II, III, and IV. Episodes of urinary frequency, both daytime and night-time, reduced significantly from baseline in all 4 groups only at 14 days of treatment. Conclusions. Bacteriophage cocktail alone or with antibiotics may improve clinical symptoms in women with chronic recurrent cystitis caused by multidrug-resistant bacterial pathogens. In addition to improving clinical symptoms, the therapy with a phage cocktail may restore antibiotic sensitivity and increase the efficacy of antimicrobial agents.